ANALISIS PENGENDALIAN PERSEDIAAN BAHAN BAKU MENGGUNAKAN METODEECONOMIC ORDER QUANTITY ( EOQ) DAN PERIODIC ORDER QUANTITY (POQ) PADA RESTO NISWADI SEKAYU - Pratiwi, Nadilah; S, Fipiariny; Satria, Rian Raga (Pusat Penelitian dan Pengabdian kepada Masyarakat, 2024)
The purpose of this Final Paper is to find out how to control the supply of raw materials at Resto Niswa, to find out the problems of controlling raw material supplies at Resto Niswa. The object of this research is Resto Niswa. The research method uses a Quantitative Descriptive method. From the results of the study it was concluded that raw material inventory control using the EOQ and POQ methods can minimize inventory costs and the frequency of ordering raw materials, where the EOQ method produces raw material inventories with a quantity of 12,857 Kg and a total inventory of RP. 13,509,949 with 7 frequency orders. Meanwhile, according to the POQ method, it produces a total inventory of 3,390 kg of raw materials with an ordering frequency of 2 times and a total inventory of Rp. 3,562,027. To Simplify inventory calculations, you can use the POM – QM application for windows.